Challenges and diagnosis of isolated left ventricular non-compaction: A case series of 4 patients with echocardiographic diagnosis of possible ILVNC - Lufundo, Nontuthuzelo; Du Toit, Hendrik; Barrett, Claire (SA Heart Journal, 2019)
Isolated left ventricular non-compaction (ILVNC) is a rare, congenital, idiopathic cardiomyopathy that may present in adulthood. There is no true gold standard for the diagnosis of ILVNC. Two-dimensional echocardiography with colour Doppler is the modality of choice to diagnose the condition. However, the diagnosis should be confirmed with cardiac magnetic resonance imaging (CMRI), as well as either a positive family history, complications of ILVNC or confirmatory genetic testing. We describe the clinical and echocardiographic features in 4 patients, each with a possible diagnosis of ILVNC, in the setting of potential alternative aetiologies for heart failure. Approval to present these cases was obtained from the institutional ethics committee and the patients also provided consent. Sufficient transthoracic echocardiographic (TTE) evidence of ILVNC according to previously published criteria was found in all the cases, although it was not confirmed with CMRI. This case series highlights the importance of routine echocardiography in all patients who present with heart failure – irrespective of associated risk factors. We caution against over-diagnosis of ILVNC with TTE alone, and recommend the use of CMRI as a second-line diagnostic investigation. Screening of family members and prevention of complications of confirmed cases of ILVNC are important.